MUSIK SEBAGAI METODE KRITIK SOSIAL-POLITIK (Analisis Perlawanan dalam Tiga Lagu Iwan Fals pada Masa Orde Baru) - Wiyanti, Zalsa Pramudya; -, Nur Hidayat -; -, Wijayanto - (Journal of Politic and Government Studies, 2024)
The phenomenon of Iwan Fals' protest music as symbolic resistance and part of the new social movement is intriguing to explore. During the New Order era, restrictions on criticism, such as media censorship, limitations on student activities via NKK/BKK, and gathering bans, reduced the space for civil society to voice opposition to the government. Iwan Fals, a mainstream musician, actively criticized the regime through protest songs like “Tikus-Tikus Kantor” and “Ambulans Zig-Zag.” His songs, such as “Suara Buat Wakil Rakyat,” were often used during demonstrations. Iwan Fals faced censorship from the regime for being perceived as "dangerous." This research aims to analyze how these three songs represent symbolic resistance and whether they fit into the framework of a new social movement. The study employs descriptive qualitative methods and Roland Barthes' semiotic analysis to decode the meaning within these songs. Theories applied include Scott's (1976) concept of symbolic resistance and Pichardo’s (1997) and Singh's (2001) theories of new social movements. Data were collected through interviews with music experts and lecturers, alongside literature review. The findings indicate that “Tikus-Tikus Kantor,” “Ambulans Zig-Zag,” and “Suara Buat Wakil Rakyat” symbolize resistance against corruption, social inequality, and the ineffectiveness of the DPR. However, these songs do not qualify as part of the new social movement due to the absence of collective action. Future studies are encouraged to investigate further